Analisis Desain Brosur Pendidikan pada Sekolah Dasar Islam Terpadu Al – Munadi Medan - Ucha Risvantry; Fuad Erdansyah (Mahesa Research Center, 2020)
This study aims to analyze the design of the SDIT AL - Munadi Medan brochure for the period 2014 - 2019 by knowing the color, layout and typography of the brochure. The research method uses descriptive qualitative by collecting various information about the brochure design of SDIT AL - Munadi Medan for the period of 2014 - 2019. The population in this study is the design of brochures for the period 2014 - 2019 amounting to 6 brochures at SDIT AL - Munadi Medan. The sample in this study used saturated sampling in which the entire population was sampled, in order to obtain data regarding the analysis of the design brochure SDIT AL - Munadi Medan. After collecting data through observation research instruments, interviews and documentation, the results of the study show the results of the SDIT AL - Munadi Medan brochure design for the period 2014 - 2019 from the color of the brochure, brochure layout, and brochure typography.